2016
DOI: 10.1186/s13148-016-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the epigenetic reader CBX2 as a potential drug target in advanced prostate cancer

Abstract: BackgroundWhile localized prostate cancer (PCa) can be effectively cured, metastatic disease inevitably progresses to a lethal state called castration-resistant prostate cancer (CRPC). Emerging evidence suggests that aberrant epigenetic repression by the polycomb group (PcG) complexes fuels PCa progression, providing novel therapeutic opportunities.ResultsIn the search for potential epigenetic drivers of CRPC, we analyzed the molecular profile of PcG members in patient-derived xenografts and clinical samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 42 publications
13
60
1
Order By: Relevance
“…In addition, PRC1 promotes cancer cell proliferation through regulating the PcG activity in cancer. Recent study has revealed that CBX2 was significantly upregulated in breast cancer and prostate cancer and may serve as a prognostic biomarker . Consistent with this previous study, our study confirmed the dramatically upregulated CBX2 in osteosarcoma and high CBX2 expression was correlated with metastasis, recurrence, and chemotherapy response, as well as unfavorable prognosis in patients with osteosarcoma.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, PRC1 promotes cancer cell proliferation through regulating the PcG activity in cancer. Recent study has revealed that CBX2 was significantly upregulated in breast cancer and prostate cancer and may serve as a prognostic biomarker . Consistent with this previous study, our study confirmed the dramatically upregulated CBX2 in osteosarcoma and high CBX2 expression was correlated with metastasis, recurrence, and chemotherapy response, as well as unfavorable prognosis in patients with osteosarcoma.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, Clermont et al reported that CBX2 silencing could inhibit cell proliferation and metastasis in prostate cancer. Moreover, CBX2 could regulate the expression of key genes involved in cancer proliferation and metastasis . These results are consistent with weaken proliferative features of CBX2‐deficient animals .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In accordance with numerous other articles, we have previously demonstrated that silencing of PcG targets can predict poor prognosis in some aggressive tumor types [5,20]. Here, we report the opposite in gastric and breast cancer, wherein an upregulation of DZNeP target genes is observed in more aggressive tumors.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…This paradigm shift has generated considerable interest in exploring the cancer epigenome in the search for clinical tools to diagnose, classify, and treat human tumors [4]. Notably, extensive evidence has demonstrated that a group of epigenetic regulators called the Polycomb Group (PcG) proteins play critical roles in human cancer and may be exploited clinically [5,6]. PcG proteins assemble in two main Polycomb Repressive Complexes (PRC1 and PRC2) known to silence key tumor suppressor genes, thereby contributing to tumorigenesis and metastasic dissemination [7].…”
Section: Introductionmentioning
confidence: 99%